Dynamic effects of oxytetracycline pollution on greenhouse gas emissions from wetlands: The synergetic regulatory roles of nutrients, DOM and microbiota - Xuecheng Wang; Yanye Li; Yang Li; Lixia Wang; Mingzhe Gao; Deshou Cun; Qichao Zhou; Junjun Chang (Journal of Environmental Chemical Engineering, 2026)

Genome-wide identification of MATE gene family in potato and functional characterization of StMATE1/4/98 in response to aluminum stress - Junjun Huang; Guanzhuo Wang; Chang Yuan; Xin Chen; Juanjuan Yu; Huiling Gong; Huahua Wang (Plant Science, 2026)

Enhancing treatment performance for agricultural runoff in ecological ditches through synergistic effects of denitrifying phosphate-accumulating bacteria and natural/synthetic media - Yonggui Zhao; Xiaoyun Sun; Bohua Ji; Ying Peng; Jingzhi Mao; Chenyu Zeng; Rui Yang; Junjun Chang (Journal of Cleaner Production, 2026)

Long-term bioaugmentation of a carrier enhanced duckweed-based wastewater treatment system via the addition of activated sludge and denitrifying phosphate-accumulating bacterium - Yonggui Zhao; Ruidong Ma; Xixi Li; Jinquan Li; Tianning Liang; Wei Li; Junjun Chang; Changqun Duan (Ecological Engineering, 2026)

Antibiotic pollution impedes nitrogen elimination rates and increases N2O emission from wetlands: A multilevel meta-analysis and the mechanisms - Jibao Jia; Yaxin Chen; Yang Li; Yuting Jiang; Deshou Cun; Yun Zhou; Shengjiong Deng; Junjun Chang (Journal of Environmental Chemical Engineering, 2026)

Increasing CO2 and CH4 emissions from constructed wetlands under composite pollution of microplastics and perfluorooctanoic acid: altering the interactions between dissolved organic matter and the functional microbiome - Yun Zhou; Mingwei Li; Shengkun Yang; Deshou Cun; Shengjiong Deng; Erik Jeppesen; Junjun Chang (Chemical Engineering Journal, 2026)

Greenhouse gas emissions from field-scale surface-flow constructed wetlands fed with different polluted water types: Environmental and microbial drivers - Deshou Cun; Xiaowan Chen; Junjun Chang; Yang Li; Rong Wu; Rufeng Lin; Shengjiong Deng; Erik Jeppesen; Changqun Duan (Journal of Hydrology, 2025)

The effect of stratus clouds on aerosol distribution in South China based on aircraft measurements - Jianqiu Gao; Zhujie Li; Junxia Li; Gang Wang; Chang Chen; Songwei He; Zhiyuan Shu; Shaoyu Hou; Junjun Lin (Atmospheric Research, 2025)

Characteristics and influencing factors of bacterial, archaeal and fungal community assemblage in riparian restored wetlands: The distinctions between the influent and effluent zones - Shengjiong Deng; Deshou Cun; Yang Li; Lixia Wang; Lingwei Kong; Junjun Chang (Process Safety and Environmental Protection, 2025)

Perfluorooctanoic acid and concomitant microplastics pollution impact nitrogen elimination processes and increase N2O emission in wetlands through regulation of the functional microbiome - Yun Zhou; Deshou Cun; Yiting Wang; Yuan Wang; Yanye Li; Erik Jeppesen; Junjun Chang (Water Research, 2025)

Effects of norfloxacin on the interaction between duckweed and its growth-promoting bacterial assemblages - Hong Lin; Junjun Chang; Tianning Liang; Chen Yang; Yingying Wei; Wei Peng; Ankun Xu; Changqun Duan; Yonggui Zhao (Journal of Hazardous Materials, 2025)

Effects of chitosan on restoring spermatogenesis in mice: Insights from gut microbiota and multi-omics analysis - Guitian He; Boqi Zhang; Tong Chen; Caomeihui Shen; Nan Wang; Junjun Yang; Fuqiang Chang; Yue Sui; Xuanqi Yin; Yueying Wang; Sihui Wang; Yaqiu Li; et al. (Food Research International, 2025)

Lake pollution control and restoration: A critical review of strategies and measures for plateau lakes in Southwestern China - Shengjiong Deng; Lingjuan Tao; Yang Li; Ping Lan; Lixia Wang; Deshou Cun; Junjun Chang (Ecological Engineering, 2025)

Acid triggering highly-efficient release of reactive oxygen species to block mitochondrial-mediated homeostasis maintenance for accelerating cell death - Yuxin Yang; Shen Wang; Xingxing Chen; Xuetao Wu; Junjun Wang; Yingcui Bu; Chang Xu; Qiong Zhang; Xiaojiao Zhu; Hongping Zhou (Analytica Chimica Acta, 2025)

Unveiling the role of intrinsic defects in N/S Co-Doped hard carbon for superior sodium-ion batteries - Yunlei Yang; Chang Liu; Junjun Yao; Zhenqi Tang; Ying Sun; Kun Zhang; Hui Li; Tianyi Ma; Jieshan Qiu (Chemical Engineering Journal, 2025)

Diurnal variations in greenhouse gas diffusive emissions from a river covered with submerged macrophytes: environmental and biotic driving factors - Haoyu Wang; Rong Wu; Deshou Cun; Yi Zhang; Yukun Hou; Junjun Chang (Aquatic Sciences, 2025)

Periodically asymmetric responses of deep chlorophyll maximum to light and thermocline in a clear monomictic lake: Insights from monthly and diel scale observations - Jingyi Li; Qichao Zhou; Yue Dao; Di Song; Zhirong Yu; Junjun Chang; Erik Jeppesen (Science of The Total Environment, 2024)

Enhanced remediation of real agricultural runoff in surface-flow constructed wetlands by coupling composite substrate-packed bio-balls, submerged plants and functional bacteria: Performance and mechanisms - Shengjiong Deng; Deshou Cun; Rufeng Lin; Dongliang Peng; Yanduo Du; Aoxue Wang; Bowen Guan; Rong Tan; Junjun Chang (Environmental Research, 2024)

Highly efficient adventitious root regeneration and Agrobacterium rhizogenes-mediated hairy root transformation in pear - Cheng Xue; Liyan Chang; Junjun Liu; Kaidi Gu; Pengfei Zheng; Jun Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Effective remediation of agricultural drainage at three influent strengths by bioaugmented constructed wetlands filled with mixture of iron‑carbon and organic solid substrates: Performance and mechanisms - Deshou Cun; Haoyu Wang; Ming Jiang; Rufeng Lin; Shengjiong Deng; Junjun Chang; Yonggui Zhao; Changqun Duan (Science of The Total Environment, 2024)

High acidity notably influences acid mine drainage treatment performance in constructed wetlands packed with composite organic substrates by affecting both abiotic and biotic routes - Deshou Cun; Shengjiong Deng; Xuan Li; Fan Yang; Junjun Chang; Pengchang Duan; Changqun Duan (Chemical Engineering Journal, 2024)

Temporal variations in dissolved organic matter properties in a eutrophic lake under water dilution and aquatic plant litter decomposition: A simulated microcosm study revealing the environmental and microbial driving factors - Rong Wu; Haoyu Wang; Wei Li; Xiaowan Chen; Qichao Zhou; Junjun Chang (Journal of Water Process Engineering, 2024)

Micro/nanoplastic pollution heterogeneously increased greenhouse gas emissions from wetlands: A multilevel meta-analysis - Yun Zhou; Deshou Cun; Haoyu Wang; Yanye Li; Junjun Chang (Journal of Cleaner Production, 2024)

Application of microbially induced calcium carbonate precipitation (MICP) process in concrete self-healing and environmental restoration to facilitate carbon neutrality: a critical review - Junjun Chang; Dongyang Yang; Cheng Lu; Zhitao Shu; Shengjiong Deng; Liwei Tan; Shaoqing Wen; Ke Huang; Pengchang Duan (Environmental Science and Pollution Research, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

Reassessing the greenhouse effect of biogenic carbon emissions in constructed wetlands - Liping Hu; Ziqian Li; Lingwei Kong; Jun Wei; Junjun Chang; Wenqing Shi (Journal of Environmental Management, 2024)

Combined treatment with pre-aeration and carrier addition strengthens the purification performance of a deep pilot-scale duckweed-based pond - Yonggui Zhao; Jinquan Li; Yuejiao Yang; Ruidong Ma; Ying Peng; Xiaoyun Sun; Siwei Gao; Junjun Chang; Changqun Duan (Journal of Water Process Engineering, 2024)

Seasonal purification efficiency, greenhouse gas emissions and microbial community characteristics of a field-scale surface-flow constructed wetland treating agricultural runoff - Xiaowan Chen; Shengjiong Deng; Bohua Ji; Suqing Wu; Junjun Chang (Journal of Environmental Management, 2023)

Agricultural runoff treatment by constructed wetlands filled with iron-carbon composites in winter: Performance augmentation by organic solids and denitrifying bacteria addition - Rufeng Lin; Yonggui Zhao; Ming Jiang; Deshou Cun; Yanwei Xiong; Yaosong Zhu; Junjun Chang (Bioresource Technology, 2023)

Urbanization shifts long‐term phenology and severity of phytoplankton blooms in an urban lake through different pathways - Yuanrui Li; Juan Tao; Yunlin Zhang; Kun Shi; Junjun Chang; Min Pan; Lirong Song; Erik Jeppesen; Qichao Zhou (Global Change Biology, 2023)
Climate change can induce phytoplankton blooms (PBs) in eutrophic lakes worldwide, and these blooms severely threaten lake ecosystems and human health. However, it is unclear how urbanization and its interaction with climate impact PBs, which has implications for the management of lakes. Here, we used multi‐source remote sensing data and integrated the Virtual‐Baseline Floating macroAlgae Height (VB‐FAH) index and OTSU threshold automatic segmentation algorithm to extract the area of PBs in Lake Dianchi, China, which has been subjected to frequent PBs and rapid urbanization in its vicinity. We further explored long‐term (2000–2021) trends in the phenological and severity metrics of PBs and quantified the contributions from urbanization, climate change, and also nutrient levels to these trends. When comparing data from 2011–2021 to 2000–2010, we found significantly advanced initiation of PBs (28.6 days) and noticeably longer duration (51.9 days) but an insignificant trend in time of disappearance. The enhancement of algal nutrient use efficiency, likely induced by increased water temperature and reduced nutrient concentrations, presumably contributed to an earlier initiation and longer duration of PBs, while there was a negative correlation between spring wind speed and the initiation of PBs. Fortunately, we found that both the area of the PBs and the frequency of severe blooms (covering more than 19.8 km 2 ) demonstrated downward trends, which could be attributed to increased wind speed and/or reduced nutrient levels. Moreover, the enhanced land surface temperature caused by urbanization altered the thermodynamic characteristics between the land and the lake, which, in turn, possibly caused an increase in local wind speed and water temperature, suggesting that urbanization can differently regulate the phenology and severity of PBs. Our findings have significant implications for the understanding of the impacts of urbanization on PB dynamics and for improving lake management practices to promote sustainable urban development under global change.

Land use regulates the spectroscopic properties and sources of dissolved organic matter in the inflowing rivers of a large plateau lake in southwestern China: implication for organic pollution control - Rong Wu; Weijie Guo; Yutong Li; Shengjiong Deng; Junjun Chang (Environmental Science and Pollution Research, 2023)

Performance and microbial community features of tidal-flow biochar-amended constructed wetlands treating sodium dodecyl sulfate (SDS)-containing greywater - Yun Zhou; Bohua Ji; Ming Jiang; Yiyang Jin; Junjun Chang (Journal of Cleaner Production, 2023)

Genetic and transcriptomic dissection of an artificially induced paired spikelets mutant of wheat (Triticum aestivum L.) - Juanyu Zhang; Yanyan Tang; Xi Pu; Xuebing Qiu; Jinhui Wang; Tao Li; Zhao Yang; Yao Zhou; Yuxiao Chang; Junjun Liang; Haili Zhang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2022)

Devonian-Carboniferous boundary in China - Wenkun Qie; Yuanlin Sun; Wen Guo; Ting Nie; Bo Chen; Junjun Song; Kun Liang; Baoan Yin; Shupeng Han; Junying Chang; Xiangdong Wang (Palaeobiodiversity and Palaeoenvironments, 2021)

Bellamya aeruginosa (Reeve) regulates bacterial community features in sediment harbouring different submerged macrophytes under different nutrient levels - Junjun Chang; Bohua Ji; Wei Li; Jianping Wu (Aquatic Sciences, 2021)

Synthesis of 4-oxotetrahydropyrimidine-1(2H)-carboxamides derivatives as capsid assembly modulators of hepatitis B virus - Nicky Hwang; Haiqun Ban; Junjun Chen; Julia Ma; Hui Liu; Patrick Lam; John Kulp; Stephan Menne; Jinhong Chang; Ju-Tao Guo; Yanming Du (Medicinal Chemistry Research, 2021)

Reporter gene knock-in into Marc-145 cells using CRISPR/Cas9-mediated homologous recombination - Yanyan Chang; Junjun Shao; Yuan Gao; Wei Liu; Zhan Gao; Yonghao Hu; Huiyun Chang (Biotechnology Letters, 2020)

Cr(VI) removal performance from aqueous solution by Pseudomonas sp. strain DC-B3 isolated from mine soil: characterization of both Cr(VI) bioreduction and total Cr biosorption processes - Junjun Chang; Shengjiong Deng; Yun Liang; Jinquan Chen (Environmental Science and Pollution Research, 2019)

Nitrogen Removal Performance and Enzyme Activities of Baffled Subsurface-Flow Constructed Wetlands with Macrophyte Biomass Addition - Junjun Chang; Shengjiong Deng; Wei Jia; Peng Chen; Yao Wang; Jinquan Chen (Water, Air, & Soil Pollution, 2018)

Greenhouse wastewater treatment by baffled subsurface-flow constructed wetlands supplemented with flower straws as carbon source in different modes - Junjun Chang; Luyao Ma; Jinquan Chen; Yifeng Lu; Xiaoyun Wang (Environmental Science and Pollution Research, 2017)

Characterization of a bovine viral diarrhea virus originated from cattle in Gansu Province, China - Shandian Gao; Junjun Shao; Junzheng Du; Tong Lin; Guozheng Cong; Furong Zhao; Huiyun Chang; Hong Yin (Virus Genes, 2013)

Enzymatic synthesis of β-N-(γ-l(+)-glutamyl)phenylhydrazine with Escherichia coli γ-glutamyltranspeptidase - Hongjuan Zhang; Yueping Zhan; Junjun Chang; Junzhong Liu; Lisheng Xu; Zhiyuan Wang; Qian Liu; Qingcai Jiao (Biotechnology Letters, 2012)

Complete nucleotide sequence of a Chinese serotype Asia1 vaccine strain of foot-and-mouth disease virus - Junzheng Du; Huiyun Chang; Guozheng Cong; Junjun Shao; Tong Lin; Youjun Shang; Zaixin Liu; Xiangtao Liu; Xuepeng Cai; Qingge Xie (Virus Genes, 2007)

Plus- and minus-stranded foot-and-mouth disease virus RNA quantified simultaneously using a novel real-time RT-PCR - Chaojiang Gu; Congyi Zheng; Lili Shi; Qian Zhang; Yong Li; Bin Lu; Yi Xiong; Sanpu Qu; Junjun Shao; Huiyun Chang (Virus Genes, 2007)